Implementasi Pengabdian Masyarakat terhadap Pengoptimalan Fungsi Taman Desa sebagai Pusat Kegiatan Masyarakat Warga Desa Pondok - Haninah Ainun Mardhiyah; Muhammad Daffa Auliarahman; Aisyah Milasari; Aldila Cahya Gayatri; Erlita Pitaloka Asmarani; Ichsan Nurrohim; Imaduddin Naufal Septahadi; Viona Rohmah Armia Gita Kusuma; Sudibya (KREASI : Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2022)
The purpose of this community service program (KKN) in Pondok Village, Karanganom District, Klaten Regency is to maximize the use of the village park in Pondok Village as a center for the activities of all people living in the area. This optimization is supported by the provision of a reading spot to support children's literacy, also held tutoring to motivate the children of the villagers to learn with interesting and fun learning, the reforestation of the park and providing additional facilities, such as the provision of a handwashing area abiding by health protocols during the pandemic; lightning and signpost provision such as toilet placards to maintain cleanliness. The program also created digital publications about the village park in the form of social media accounts that can provide information related to the activities in the park. The participants of these activities are group 04, KKN Tematik Membangun Desa. The results of this activity are optimization in utilizing the village park as a center of activities for Pondok Village residents as well as encouraging the realization of the village’s ambition to be a tourist site in Klaten Regency.